In-cylinder soot radiation heat transfer in direct-injection diesel engines. (December 2015) - Benajes, Jesús; Martín, Jaime; García, Antonio; Villalta, David; Warey, Alok
Highlights: Optoelectronic pyrometer provides similar results compared with a conventional method. Lower injection pressure results in higher radiation. Higher ambient temperature and higher in-cylinder gas density produce higher radiation. Larger lift-off length reduces the soot volume fraction and the spectral intensity. An increase on swirl number, load and CA50 provide a lower total radiation. Lower values of EGR implies a decreased on radiation intensity. Abstract: The efficiency and CO2 are one of the main concerns of automotive manufacturers. There are several strategies under investigation to solve this problem. In the present work, the research effort has been focused on improving knowledge of in-cylinder heat transfer and its impact on engine efficiency. In particular, soot radiation was studied since it can be considered a significant source of the efficiency losses in modern diesel engines. Considering previous studies, the portion of total chemical energy released during combustion lost due to radiation heat transfer varies widely from 0.5% up to 10%, depending on engine parameters and combustion process. Thus, the main objective of this work was to evaluate the amount of energy lost to soot radiation relative to the input fuel chemical energy during the combustion event under different operating conditions in a completely controlled environment provided by an optical engine. Under these simplified conditions, two-color method was applied by using high speed imaging pyrometer with cameras (two dimensional results) and optoelectronic pyrometer (zero dimensional results). Once a detailed comparison between both diagnostics was performed, optoelectronic pyrometer was used to characterize radiant energy losses in a fully instrumented 4-cylinder direct-injection light-duty diesel engine. In particular swirl ratio, EGR and combustion phasing effects on radiation heat transfer were evaluated.